Associação entre gestão, recursos humanos e cuidados prestados a pacientes com necessidades especiais de saúde em Centros de Especialidades Odontológicas no Brasil: um estudo transversal - Jennifer Reis de Oliveira (2023)
This study aimed to identify the association between management and human resource factors with the performance of dental care provided to patients with special health care needs (SHCN) in secondary care in Brazil in the second cycle of the Program for Quality Improvement and Access to Dental Specialty Centers (PMAQ-CEO). Secondary data analysis from the second cycle from PMAQ-CEO, which evaluated 1,097 Dental Specialty Centers (DSCs), conducted in 2018. Seventeen independent variables taken from dentists’ training, and dental team management characteristics were analyzed to assess their influence on the reported "Performance of care for SHCN patients". An estimated score was generated from their performance on 23 questions related to the physical and human structure and work processes in the oral health care of SHCN patients in the DSCs. Negative binomial regression model with values p≤0.05 were considered significant. Data analysis included residual deviation to the degree of freedom and the chi-square test. The patient care performance score with SHCN increases significantly when the DSC has a manager (RR=1.019; CI=1.011-1.026) and goal monitoring and analysis (RR=1.012; CI=1.007-1.005). By contrast, the DSCs in which the dentist is a statutory public servant (RR=0.998; CI=0.997-1.000) and performs additional unhealthy or hazardous duties (RR=0.998; CI=0.996-0.999) are less likely to provide a higher quality care. The heterogeneity and low performance scores for dental care provided to SHCN was identified in Brazilian health services. It was possible to verify that management and human resource factors of the DSCs were associated with the performance of dental care provided to SHCN patients.